2022
DOI: 10.1186/s12893-022-01840-4
|View full text |Cite
|
Sign up to set email alerts
|

BMI and pelvimetry help to predict the duration of laparoscopic resection for low and middle rectal cancer

Abstract: Background In rectal cancer surgery, recent studies have found associations between clinical factors, especially pelvic parameters, and surgical difficulty; however, their findings are inconsistent because the studies use different criteria. This study aimed to evaluate common clinical factors that influence the operative time for the laparoscopic anterior resection of low and middle rectal cancer. Methods Patients who underwent laparoscopic radica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In a previous study by Kawai et al, body weight has been found to be correlated with lengthened SFM in univariable analysis, but the study does not include BMI and height. On the other hand, although several studies have shown that increased BMI is associated with di cult operation scores, lengthened operation time and increased risk for conversion during laparoscopic rectal cancer surgery, they have not speci cally investigated the correlation between SFM duration and BMI (17)(18)(19). The current study has demonstrated that higher BMI and weight may be indicators for lengthened SFM.…”
Section: Discussionmentioning
confidence: 57%
“…In a previous study by Kawai et al, body weight has been found to be correlated with lengthened SFM in univariable analysis, but the study does not include BMI and height. On the other hand, although several studies have shown that increased BMI is associated with di cult operation scores, lengthened operation time and increased risk for conversion during laparoscopic rectal cancer surgery, they have not speci cally investigated the correlation between SFM duration and BMI (17)(18)(19). The current study has demonstrated that higher BMI and weight may be indicators for lengthened SFM.…”
Section: Discussionmentioning
confidence: 57%
“…Some patients underwent ileostomy at the same time of resection. In order to reduce the impact of this operation, the operation time of these patients was recorded as the initial time minus 15 minutes ( 17 ). When the entire operation cannot be completed by laparoscopy, it should be changed to acombined approach (transabdominal and transanal surgery).…”
Section: Methodsmentioning
confidence: 99%